2016
DOI: 10.3758/s13414-016-1223-3
|View full text |Cite
|
Sign up to set email alerts
|

Figural properties are prioritized for search under conditions of uncertainty: Setting boundary conditions on claims that figures automatically attract attention

Abstract: Nelson and Palmer (2007) concluded that figures/figural properties automatically attract attention after finding that participants were faster to detect/discriminate targets appearing where a portion of a familiar object was suggested in an otherwise ambiguous display. We investigated whether these effects are truly automatic and whether they generalize to another figural propertyconvexity. We found that Nelson and Palmer's results do generalize to convexity but only when participants are uncertain regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Given that attention has been conceptualized in numerous ways (Hommel et al, 2019), it is to be noted that here "attention" may be operating to prioritize some stimulus attributes before the outcome of perceptual organization is determined, a mechanism that can be described as "priming." It has been hypothesized that attention can operate by prioritizing certain stimulus attributes (Gottlieb, 2012;Peterson et al, 2017;Shomstein, 2012;Shomstein & Yantis, 2004). Our data support the hypothesis that the instructions to pay attention to the potential presence of familiar shapes upweighted the influence of familiar parts as well as familiar configurations.…”
Section: Discussionsupporting
confidence: 85%
“…Given that attention has been conceptualized in numerous ways (Hommel et al, 2019), it is to be noted that here "attention" may be operating to prioritize some stimulus attributes before the outcome of perceptual organization is determined, a mechanism that can be described as "priming." It has been hypothesized that attention can operate by prioritizing certain stimulus attributes (Gottlieb, 2012;Peterson et al, 2017;Shomstein, 2012;Shomstein & Yantis, 2004). Our data support the hypothesis that the instructions to pay attention to the potential presence of familiar shapes upweighted the influence of familiar parts as well as familiar configurations.…”
Section: Discussionsupporting
confidence: 85%
“…Some have claimed that attention is automatically allocated to familiar over novel objects 29 . Yet a recent study 30 showed that previous results taken to support this claim were replicated only under conditions of search involving spatiotemporal uncertainty 31,32 . Our experiments did not involve search nor was spatiotemporal uncertainty present: each stimulus was shown in one of only two locations at a fixed interval after trial onset; hence it is unlikely that attention was automatically allocated toward the familiar object.…”
Section: Discussionmentioning
confidence: 96%
“…Some have claimed that attention is automatically allocated to familiar over novel objects 26 . Yet a recent study 27 showed that previous results taken to support this claim were replicated only under conditions of target search involving spatiotemporal uncertainty and concluded that figural properties (e.g., familiarity, convexity, etc.) can be entered into a task-dependent attentional priority map 28,29 .…”
Section: Discussionmentioning
confidence: 98%